Gestión energética para una óptima respuesta a la demanda en micro redes inteligentes. - Jarrín Vinueza, David Salomón (2017)
In this document, we develop a model of energy management, to encourage users and customers to optimize demand, considering that, customers are connected by smart microchip with all the benefit it carries. "The price of real energy" is the mechanism used to give and respond to demand, which aims to transfer to customers the actual cost of electric power. It is necessary through Markov chains, it would have the possible demands in the next moment (in the next hour in general), and according to the demands, makes an economic delivery of the Distributed Generation plants, obtaining the real energetic cost. As a result of the management model, obtaining unic and different dynamic rates for each customer, with ranges of energy and power with each energy price. This rate is updated every hour, according to the historical demand of each client. The Management Model looks for customers to modify their customs amounts, with the objective of reducing the total price to be paid, helping to flatten the load of the curve and reducing the total cost of the electrical system.